Further techniques for coaching and mentoring - Megginson, David, 1943- (Butterworth-Heinemann, 2009)
Building on the success of companion volume Techniques for Coaching and Mentoring, this new volume from coaching gurus David Clutterbuck and David Megginson is a practical, pragmatic guide to the knowledge and techniques you need for successful coaching and mentoring. Rather than adopting a particular school of coaching or mentoring, the authors pick the best from a range of models and frameworks that have developed since the first book published to help you enrich your practice. Further Techniques also features a new structure to make it more reader-friendly, with Part 1 putting the techniques.